Dissociation of carbon dioxide in arrays of microchannel plasmas. (14th January 2019) - Shin, C; Oh, T; Houlahan, T J; Fann, C-H; Park, S-J; Eden, J G
Abstract: Energy efficiencies above η = 12% have been observed for the nonthermal dissociation of pure carbon dioxide (i.e. in the absence of carrier gas) at atmospheric pressure in arrays of microchannel plasmas. Microplasma 'chips' similar to those developed for the plasmachemical production of ozone from O2 or air (Kim et al 2017 Eur. Phys. J. Spec. Top . 226 2923) generate spatially uniform, abnormal glow plasmas in ⩾ 1 atm. of CO2 and consume 1–8 W of average power when driven by sinusoidal or bipolar pulsed voltage waveforms (pulse repetition frequency of 15–20 kHz). Fabricated in nanoporous alumina, the microchannels are 250 µ m in width, 150 µ m in depth, and 3 cm in length, and the array on each chip typically comprises 12 channels. Intense emission from microplasma arrays, recorded over the 335–700 nm spectral interval when E / N ≈ 100 Td, is dominated by fluorescence which indicates that both and electronically-excited CO (e.g. CO * ) are generated primarily by multistep electron impact processes. Dissociative recombination of the ground state species appears to also be a contributing factor in CO * production. Owing to the modest power consumption and active volume of a single chip, the CO generation efficiency for a single array is 45 g kWh −1 for a CO2 flow rate of 70 sccm and the dissociation efficiency is 4.3%. The connection of four chips in tandem in a commercial module increases the CO2 dissociation efficiency to 20% and 11% for flow rates of 70 sccm and 200 sccm, respectively. Data acquired with multiple chips confirms the scalability of the CO2 dissociation process, and suggests the economic viability of the commercial production of CO for the synthesis of formic acid, methanol, and syngas.